Enhancing the Digital Earth via Digital Decimal Geolocation and the FAIR Data Principles - W. Brian Whalley (Earth Science, Systems and Society)
The essential aspects of Gore’s “Digital Earth” concept include “georeferenced” data. This paper is concerned with establishing the need for a standardised and common form to locate points on the earth’s surface. Rather than a degree, minute, second (dms) system for latitude/longitude location, a decimal degree system, formatted as a comma separated variable tuple in square brackets, [dLL], is advocated. Values, to an appropriate number of decimal places, can be inserted in text to be computer searchable. The [dLL] also becomes metadata for a data set or as an index in databases or identifiers for images. Various uses of this system are illustrated. The [dLL] allows data to become more “open” via the FAIR data principles: findability, accessibility, interoperability, and reusability. Wider use of [dLL] in the earth sciences is fundamental to collaboration with other disciplines, especially Critical Zone Science. The general use of [dLL] geolocation can be exploited in a wide variety of data analytical methodologies, some of which are outlined, and in earth science and environmental data situations.